SELECTION OF SUPERIOR EMPLOYEES USING THE PROFILE MATCHING APPROACH IN THE SALES DECISION SUPPORT SYSTEM AT AKUL CATERING - Rima Tamara Aldisa; Mohammad Aldinugroho Abdullah, Puspa Ayu Sholeha (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Identifying and recruiting superior employees is a good challenge for every organization, including catering businesses where service quality directly influences customer satisfaction and business success. This research aims to develop a Decision Support System (DSS) using the Profile Matching approach to facilitate the selection of superior employees at Akul Catering. The Profile Matching method is used to assess the suitability between the candidate's competency profile and the competency profile required by the position to be filled. This research designs and implements an algorithm to measure the level of such matches, enabling more objective and efficient decision making. Data was collected through observation, interviews and questionnaires to determine the criteria and sub-criteria that are relevant to the positions available at Akul catering. The results of this research show that the developed system can effectively speed up the selection process by filtering out candidates who do not meet the minimum criteria and identifying candidates with the best profile match. It is hoped that this system can be integrated into the recruitment process at Catering Akul well to improve employee quality and overall improve catering performance.